William Penn and early quakerism - Endy, Melvin B. (Princeton, New Jersey : Princeton University Press, 1973)
William Penn is justly famous for his part in the political development of colonial America. Yet he was also one of the leading Quaker theologians of the seventeenth century and the most important translator of Quaker religious thought into social and political reality, and his life and works cannot be fully understood without a knowledge of his religious hopes and ideals. Melvin Endy goes beyond the political histories, biographies, and histories of Quakerism to provide a comprehensive account of Penn's religious thought, its influence on his political thought and activity, and the significance of his life and thought to the Quaker movement. His assessment of Penn's place in the Quaker movement and his discussion of Penn's thought in relation to Puritan, Spiritualist. Anglican, and pre-Enlightenment developments has led to an understanding of Quakerism that differs from the recent tendency to stress strongly its Puritan origins and affinities. Because of the revisionist nature of this interpretation and the author's conviction that early Quaker thought has never been adequately related to its intellectual milieu, this study of Penn has been developed into a vehicle for a new analysis of aspects of early Quaker thought. Finally, the Pennsylvania venture is examined and assessed as a laboratory in which the vision of a society run according to the principles of a spiritual religion was put to the test.Originally published in 1973.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- PREFACE -- TABLE OF CONTENTS -- INTRODUCTION -- ONE: THE PREHISTORY OF QUAKERISM: PURITANISM AND SPIRITUALISM -- TWO: THE SPIRITUAL RELIGION OF THE EARLIEST QUAKERS -- THREE: WILLIAM PENN T H E QUAKER -- FOUR: THE DEVELOPED RELIGION OF THE SPIRIT -- FIVE: SPIRITUAL RELIGION AND RATIONALISM -- SIX: SPIRITUAL RELIGION AND THE CHRISTIAN GOSPEL -- SEVEN: SPIRITUAL RELIGION AND THE KINGDOM OF GOD -- EIGHT: THE KINGDOM COME: PENNSYLVANIA -- SELECTED BIBLIOGRAPHY -- INDEX
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Penn, William, -- 1644-1718.; Penn, William, -- 1644-1718.; Penn, William, -- 1644-1718; Society of Friends -- History; Société des Amis -- Histoire; BIOGRAPHY & AUTOBIOGRAPHY -- General; RELIGION -- Christianity -- Denominations; Society of Friends; History